Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
c.
\(\frac{1}{3}\times\frac{5}{7}-\frac{7}{27}\times\frac{36}{14}\)
\(=\frac{1}{3}\times\frac{5}{7}-\frac{7}{3\times9}\times\frac{4\times9}{7\times2}\)
\(=\frac{1}{3}\times\frac{5}{7}-\frac{1}{3}\times\frac{4}{6}\)
\(=\frac{1}{3}\times\left(\frac{5}{7}-\frac{4}{6}\right)\)
\(=\frac{1}{3}\times\left(\frac{30-38}{42}\right)\)
\(=\frac{1}{3}\times\frac{-8}{42}\)
\(=-\frac{4}{63}\)
Chúc bạn học tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(\frac{-1}{6}+\frac{5}{-12}\right)+\frac{7}{12}=\left(\frac{-2}{12}+\frac{-5}{12}\right)+\frac{7}{12}=\left(\frac{-7}{12}\right)+\frac{7}{12}=0\)
b)\(\frac{7}{36}-\frac{8}{-9}+\frac{-2}{3}=\frac{7}{36}+\frac{32}{36}-\frac{24}{36}=\frac{15}{36}=\frac{5}{12}\)
c) \(\frac{3}{5}-\frac{2}{5}.\frac{10}{12}=\frac{3}{5}-\frac{2}{5}.\frac{5}{6}=\frac{3}{5}-\frac{1}{3}=\frac{9}{15}-\frac{5}{15}=\frac{4}{15}\)
d) \(\frac{2}{\left(-3\right)^2}+\frac{5}{-13}-\frac{-3}{4}=\frac{2}{9}-\frac{5}{13}+\frac{3}{4}=\frac{8}{36}-\frac{15}{36}+\frac{27}{36}=\frac{5}{9}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
9:
\(=5+\dfrac{1}{5}-\dfrac{2}{9}-2+\dfrac{1}{23}+\dfrac{73}{35}-\dfrac{5}{6}-8-\dfrac{2}{7}+\dfrac{1}{18}\)
\(=\left(5-2-8\right)+\left(\dfrac{1}{5}+\dfrac{73}{35}-\dfrac{2}{7}\right)+\left(-\dfrac{2}{9}+\dfrac{1}{18}-\dfrac{5}{6}\right)+\dfrac{1}{23}\)
\(=\left(-5\right)+\dfrac{7+73-10}{35}+\dfrac{-4+1-15}{18}+\dfrac{1}{23}\)
\(=-5+2-1+\dfrac{1}{23}=-4+\dfrac{1}{23}=-\dfrac{91}{23}\)
10: \(=\left(\dfrac{1}{3}+\dfrac{3}{5}+\dfrac{1}{15}\right)+\left(\dfrac{-3}{4}-\dfrac{2}{9}-\dfrac{1}{36}\right)+\dfrac{1}{64}\)
\(=\dfrac{5+9+1}{15}+\dfrac{-27-8-1}{36}+\dfrac{1}{64}\)
=1/64
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{-5}{8}\cdot\left(\frac{4}{9}+\frac{-7}{12}\right)\)
\(=\frac{-5}{8}\cdot\frac{-5}{36}\)
\(=\frac{25}{288}\)
b) \(\left(-3,2\right)\cdot\frac{-15}{64}+\left(0,8-2\frac{4}{5}\right):3\frac{1}{2}\)
\(=\frac{3}{4}+\left(-2\right):\frac{7}{2}\)
\(=\frac{3}{4}+\frac{-4}{7}\)
\(=\frac{5}{28}\)
=))
a, 3 5 - 10 2 : 5 2 + 2 3 . 7 = 243 - 100:25+8.7 = 243 - 4+56 = 239+56 = 295
b, 36 . 57 - 36 . 35 + 64 . 62 - 64 . 40 = 36(57 - 35)+64(62 - 40)
= 36.22+64.22 = 22.(36+64) = 22.100 = 2200